An Overview of the Legal Regime Governing Minerals in Ethiopia - Weldie, Tilahun Hindeya (Bahir Dar University Journal of Law, 2022)
AbstractThe contribution of the mining sector to the Ethiopian economy has been dismal. Thissituation is being reversed with the mining sector’s contribution to the Ethiopianeconomy growing significantly in recent years reflecting the sector’s potential to spurthe economic growth of the country. Many factors including the legal reforms thathave taken place over the last two decades played major roles for the growth of themining sector’s contribution to the Ethiopian economy. This article addresses thecurrent legal framework governing minerals in Ethiopia. It examines the extent towhich the laws try to strike a balance between the rights of investors and the publicinterest with a particular focus on social and environmental considerations. The overallexamination and analysis reveal that while the legal reforms have undergonea substantial transformation to allure investors in the sector, some problems related tothe implementation of rights and obligations remain a concern. Moreover, social andenvironmental considerations are also poorly addressed.